Managing the impact of international financial reporting standards on audit and non-audit fees: Some empirical findings and ethical discussions - Abdul Rashid, Hafiz Majdi; Wan Lokman, Wan Abdul Wahid; Annuar, Hairul Azlan; Hamdan, Hamdino (Universiti Tenaga Nasional., 2017)
The aim of this study is to examine the association between IFRS adoption (in the context of Malaysia, MASB aligns its standards substantially with the IFRS requirements and called the standards as MFRS) and audit and non-audit fees paid to external auditors in Malaysia. The sample companies are 166 companies listed on Bursa Malaysia for the financial year ended 2006 (i.e. the first year which the MASB converged its standards to IFRS). The results reveal that IFRS adoption is positively and significantly associated with statutory audit fees. The results are consistent with the literature which suggests IFRS adoption will result in increased scope of work and responsibility of the external auditors, which finally entails additional costs. However, there is no evidence to support the hypothesis that non-audit fees are positively and significantly associated with IFRS adoption. Therefore, the suspected ethical dilemma on auditor independence in the case of IFRS adoption is not supported by the empirical results. Hence, in order to control the potential increase in audit fees charged, the accounting regulators such as Malaysia Institute of Accountants (MIA) and Malaysia Accounting Standard Board (MASB) should provide clearer guidelines in interpreting and understanding the newly adopted IFRS.